BUREAUCRATIC ISLAM COMPARED: CLASSIFICATORY POWER and STATE-IFIED RELIGIOUS MEANING-MAKING in BRUNEI and SINGAPORE - Mueller, Dominik M. (The Journal of Law and Religion, 2018)
This article presents a comparative anthropological approach to studying the bureaucratization of Islam in contemporary Southeast Asia. In line with this approach, the article understands the bureaucratization of Islam not simply as a formalization, expansion, and diversification of Islamic institutions and legal frameworks; rather, bureaucratization is investigated as a social phenomenon that transcends its organizational boundaries and informs dynamics of socio-legal change alongside transformations of the meaning(s) of Islam in state and society. The article centers the state's classificatory power and its societal coproduction and contestation, and it takes both functional and hermeneutic modes of analysis into consideration. While the bureaucratization of Islam is always embedded in and shaped by power-political constellations, it simultaneously produces social and doctrinal meanings that are unique to its locally specific discursive arenas. Therefore, more conventional functional perspectives on bureaucratic Islam can be beneficially enriched by a more hermeneutically oriented anthropological analysis, as the article illustrates, based on ethnographic data gathered in Brunei and Singapore. The article first introduces the anthropology of bureaucracy and elaborates on the absence of such studies on state-Islam relations in Southeast Asia, as well as the potential of bringing these streams of scholarship into a fruitful dialogue. Second, it presents the Bruneian case study, focusing on postcolonial Islamization policies, the bureaucratization of a national ideology, legal reforms, and their workings on the microlevel. Third, it moves on to a regional comparison, by illustrating how Islamic knowledge and meaning-production inherent to the bureaucratization of Islam unfolds quite differently in Singapore, despite partly overlapping functional patterns. While anchored in Brunei and Singapore, the article offers a conceptual framework and analytic vocabulary for a wider study across and potentially beyond the region.
Created from Fastlane, Scopus look-up
Keywords: Brunei; bureaucracy; classificatory power; Islam; law and social change; Singapore; Southeast Asia